ANALYSIS OF THE IMPACT OF SOCIAL MEDIA MARKETING, SERVICE QUALITY, AND SALES ACTIVITIES ON THE INCREASE IN SALES OF PROBLEMATIC FINANCING GUARANTEES (DEFAULT) THROUGH AUCTION: CASE STUDY AT ABC ISLAMIC BANK - Rani Ayu Asari; Sri Hartini (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The study's purpose is to assess and disseminate the effect of the interaction between Social Media Marketing components, Quality, and Sales Activities on increasing the sales of customer guarantees for problem financing (losses) through auctions at ABC Service Sharia Bank. This study employs quantitative methodologies with a population of all workers of PT Bank Syariah ABC and a random sample of 30 respondents from Bank Syariah ABC employees in the Surabaya region. Data collection methods use questionnaires, case studies and interviews. The data analysis approach includes performing “Data Quality Tests”, “Classic Assumption Tests”, “Multiple Linear Regression Tests”, and “Hypothesis Testing”. Based on this study, the components of Social Media Marketing, Service Quality and Sales Activity, both on their own and in combination, have a notable influence on increasing sales of collateral for non-performing financing customers through auctions: Case Study at ABC Sharia Bank. The managerial implications for PT Bank Syariah ABC resulting from this research include optimizing the implementation or running of the three components above so that sales of customer collateral through auctions can increase significantly so that the rate of return or recovery of problematic/defaulting customers is reduced.